Spatial and Management Characteristics and their Relationship with Borehole Functionality in the Eastern Region, Ghana. - Schultes, Olivia L. (Tufts Archival Research Center, 2018)
Improved water infrastructure, such as boreholes, contribute to improved health outcomes in rural, low-income settings by increasing the quality and quantity of available drinking water. However, boreholes must be functional to produce the associated health benefits, and an estimated 36% of water systems in sub-Saharan Africa are non-functional. Management and spatial characteristics are thought to affect the ability and motivation of communities to maintain and repair boreholes. In this study, water infrastructure, housing, and survey data were collected from 15 towns in the Eastern Region, Ghana. Borehole functionality was measured using longitudinal data from 3 years. There were a variety of management structures and practices utilized by the study communities, but none of them were significantly correlated with BH functionality. User-reported payment was high (93%) and was positively correlated with BH functionality. Distance to nearby houses and water sources was not correlated to BH functionality. This study revealed that missing BH data was prevalent and spatially biased, which has implications for future cross-sectional studies.